2022
DOI: 10.3390/life12010055
|View full text |Cite
|
Sign up to set email alerts
|

Blue Laser Light Counteracts HSV-1 in the SH-SY5Y Neuronal Cell Model of Infection

Abstract: Herpes simplex virus 1 (HSV-1) is wide-spread virus that triggers painful and recurrent infections, as herpes labialis, causing blister lesions on the lip. HSV-1 infection can be a lifelong condition starting from childhood due to the latency of the virus hidden in the trigeminal ganglia. Despite the use of antiviral treatments, there is not a resolutive cure for herpes. In our study, we tested blue light against HSV-1 in a neuronal cellular model, aimed at mimicking the neuronal tropism of HSV-1. Two laser pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…SH-SY5Y is a human-derived cell of neural tissue origin. In this experiment, seven new iridoid compounds were screened for antiviral activity, and it was found that officinaloside C has good anti-HSV-1 activity on SH-SY5Y cells [ 25 ]. This helps to understand the virulence of officinaloside C in anti-HSV-1-infection, especially herpes encephalitis caused by anti-HSV-1-infection.…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y is a human-derived cell of neural tissue origin. In this experiment, seven new iridoid compounds were screened for antiviral activity, and it was found that officinaloside C has good anti-HSV-1 activity on SH-SY5Y cells [ 25 ]. This helps to understand the virulence of officinaloside C in anti-HSV-1-infection, especially herpes encephalitis caused by anti-HSV-1-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Blue light was also described as effective in counteracting HCoV‐229 E, HCoV‐OC43 [ 14 ], SARS‐CoV‐1, MERS‐CoV [ 11 ], HSV‐1 [ 15 , 16 ], and Zika virus [ 17 ].…”
Section: Introductionmentioning
confidence: 99%